Note from the editor-in-chief: toward a more creative education - Ikhsanudin Ikhsanudin (UPT Bahasa Universitas Tanjungpura, 2019)
Changes in society need creative changes in education, including in English language teaching and learning. Society 5.0 needs more creative educators and researchers to help learners getting prepared for the future. This journal’s first volume (issues 1 and 2) reports fourteen creative studies and a review. In the next issues, more creative and innovative studies need to be done to open new horizons of language creative uses, innovations in language teaching, and innovations in teaching materials.